2021
DOI: 10.1097/md.0000000000025308
|View full text |Cite
|
Sign up to set email alerts
|

Short- and long-term outcomes of 486 consecutive laparoscopic splenectomy in a single institution

Abstract: Since its introduction in 1991, laparoscopic splenectomy (LS) has become the gold standard in elective spleen surgery in many centres. However, there still lack the report of long-term outcomes of LS with the large-scale cases. The aim of the present study was to analyze the short- and long-term outcomes of LS in a single institution over 16 years, and to compare the perioperative outcomes of totally laparoscopic splenectomy (TLS) and hand-assisted laparoscopic splenectomy (HALS) for splenomegaly. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 31 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…The oncological safety of a minimally invasive approach for spleen malignancies (including SM) was recently demonstrated [102]. A minimally invasive splenectomy is associated with low morbidity rates and almost nil mortality rates for both benign and malignant pathologies [102,103], although a malignant pathology is a risk factor for postoperative morbidity [104].…”
Section: Discussionmentioning
confidence: 99%
“…The oncological safety of a minimally invasive approach for spleen malignancies (including SM) was recently demonstrated [102]. A minimally invasive splenectomy is associated with low morbidity rates and almost nil mortality rates for both benign and malignant pathologies [102,103], although a malignant pathology is a risk factor for postoperative morbidity [104].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Violi et al described a prevalence of PVT of 17% in cirrhotic patients overall, corresponding to 11.3% in Child-Pugh A class, 24.8% in Child-Pugh B and 17.2% in Child-Pugh C [38]. A recently published study evaluating 486 consecutive laparoscopic splenectomies reported post-operative portal vein system thrombosis in 19.8% of cases [39]. The high prevalence of SVT together with the observational design of the included studies indicate that there might be a bias in the enrolled population, suggesting that D-dimer was tested in patients more likely to develop SVT among those at high risk.…”
Section: Discussionmentioning
confidence: 99%